Prognostic serum biomarkers of synaptic, neuronal and glial injury in patients with acute ischemic stroke of the anterior circulation - Barba, Lorenzo; Vollmuth, Christoph; Halbgebauer, Steffen; Ungethüm, Kathrin; Hametner, Christian; Essig, Fabian; Kollikowski, Alexander Marco; Pham, Mirko; Schuhmann, Michael K.; Heuschmann, Peter U.; Oeckl, Patrick; Steinacker, Petra; et al. (European journal of neurology, 2025)
Background We aimed to investigate the prognostic role of β-synuclein in comparison to that of neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) for predicting functional outcome after acute ischemic stroke (AIS). Methods We measured serum concentrations of β-synuclein, NfL and GFAP 24 h after hospital admission in 213 consecutive patients with moderate-to-severe AIS. We investigated the association between serum biomarkers and radiological/clinical characteristics, 3-months mortality and functional outcome on the modified Rankin Scale (mRS). Results In 213 patients with AIS [mean age: 76.1 (±12.5) years, 53.1% males, median NIHSS score on admission: 13 (IQR: 9-17)], higher levels of β-synuclein, NfL and GFAP were associated with higher NIHSS scores and with lower Alberta Stroke Program CT Score (ASPECTS) points on admission. Serum β-synuclein levels was significantly correlated with NfL (rho = 0.715, p < 0.001) and GFAP concentrations (rho = 0.684, p < 0.001). The inclusion of serum β-synuclein significantly improved the accuracy of prediction models without biomarkers for overall mortality (AUC: 0.836 vs. 0.752, p < 0.001) and mRS 3-6 vs. 0-2 (AUC: 0.812 vs. 0.624, p < 0.001). Combination models with NfL and/or GFAP showed a similar accuracy. Conclusions Serum β-synuclein may be used to assess synaptic damage/dysfunction and to predict 3-months clinical outcomes in patients with AIS.